ORGANIZATIONAL AND ECONOMIC PROBLEMS BETWEEN FARMS AND INFRASTRUCTURE SUBJECTS - Rustambek Imomov (Antis Publisher, 2024)
Objective: The study highlights critical challenges in the agricultural sector, particularly focusing on imbalances in the provision of material and technical resources to farms. Additionally, it examines the effects of monopolistic practices in resource production and supply, which exacerbate these imbalances and hinder sectoral growth. Method: A qualitative approach was employed, involving an in-depth analysis of resource allocation systems and supply chain structures within the agricultural industry. Data were collected from various case studies and reports to understand the extent and impact of resource imbalances and monopolistic tendencies. Results: Findings reveal that a significant disparity exists in the availability and distribution of essential resources, disproportionately affecting small-scale farmers. The monopolistic control over resource production and distribution further aggravates the issue, leading to inefficiencies and increased costs for farmers. These challenges collectively contribute to stagnation in agricultural productivity and sustainability. Novelty: This research underscores the dual impact of resource imbalances and monopolistic practices as interconnected issues, rather than treating them as isolated problems. By identifying their combined influence, the study offers a comprehensive perspective on systemic challenges in agriculture, paving the way for more targeted interventions and policy reforms.